Impact of Non-Human Leukocyte Antigen-Specific Antibodies in Kidney and Heart Transplantation - Zhang, Xiaohai; Reinsmoen, Nancy L. (Frontiers in Immunology, 2017)
The presence of donor human leukocyte antigen (HLA)-specific antibodies has been shown to be associated with graft loss and decreased patient survival, but it is not uncommon that donor-specific HLA antibodies are absent in patients with biopsy-proven antibody-mediated rejection. In this review, we focus on the latest findings on antibodies against non-HLA antigens in kidney and heart transplantation. These non-HLA antigens include myosin, vimentin, Kα1 tubulin, collagen, and angiotensin II type 1 receptor. It is suggested that the detrimental effects of HLA antibodies and non-HLA antibodies synergize together to impact graft outcome. Injury of graft by HLA antibodies can cause the exposure of neo-antigens which in turn stimulate the production of antibodies against non-HLA antigens. On the other hand, the presence of non-HLA antibodies may increase the risk for a patient to develop HLA-specific antibodies. These findings indicate it is imperative to stratify the patient’s immunologic risk by assessing both HLA and non-HLA antibodies.